2005
DOI: 10.1104/pp.105.065458
|View full text |Cite
|
Sign up to set email alerts
|

A Lily ASR Protein Involves Abscisic Acid Signaling and Confers Drought and Salt Resistance in Arabidopsis

Abstract: LLA23, an abscisic acid-, stress-, and ripening-induced protein, was previously isolated from lily (Lilium longiflorum) pollen. The expression of LLA23 is induced under the application of abscisic acid (ABA), NaCl, or dehydration. To provide evidence on the biological role of LLA23 proteins against drought, we used an overexpression approach in Arabidopsis (Arabidopsis thaliana). Constitutive overexpression of LLA23 under the cauliflower mosaic virus 35S promoter confers reduced sensitivity to ABA in Arabidops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
111
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 58 publications
6
111
0
1
Order By: Relevance
“…ASR overexpression studies in plants are exemplified by works carried out on Solanoideae (Kalifa et al, 2004b;Frankel et al, 2007) and Arabidopsis, although the latter does not include any ASR homologous genes (Yang et al, 2005;Liu et al, 2010). Our study demonstrated that ZmASR1-OE improved the kernel yield of transgenic maize in the field under well-watered and water-limited conditions.…”
Section: Zmasr1 Maintained Kernel Yield Under Water Deficit Conditionmentioning
confidence: 86%
See 2 more Smart Citations
“…ASR overexpression studies in plants are exemplified by works carried out on Solanoideae (Kalifa et al, 2004b;Frankel et al, 2007) and Arabidopsis, although the latter does not include any ASR homologous genes (Yang et al, 2005;Liu et al, 2010). Our study demonstrated that ZmASR1-OE improved the kernel yield of transgenic maize in the field under well-watered and water-limited conditions.…”
Section: Zmasr1 Maintained Kernel Yield Under Water Deficit Conditionmentioning
confidence: 86%
“…These associations were validated by the observation that transgenic maize lines misexpressing ZmASR1 showed significant changes in leaf senescence under mild water deficit conditions in the field (Jeanneau et al, 2002). Interestingly, transgenic Arabidopsis (Arabidopsis thaliana) plants overexpressing an ASR gene from Lilium longiflorum (LLA23) or banana (Musa paradisiaca; MpASR) exhibited enhanced capacity to survive in water-limited conditions (Yang et al, 2005;Liu et al, 2010). Overexpression of the tomato (Solanum lycopersicum) ASR1 gene (SlASR1) in tobacco (Nicotiana tabacum) plants also resulted in decreased rates of water loss (Kalifa et al, 2004b).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…For example, over-expression of tomato ASR1 and lily ASR increases salt tolerance in tobacco (Kalifa, 2004) and Arabidopsis (Yang et al, 2005), respectively. ASR1-overexpressing transgenic (TG) tobacco plants showed increased expression of different genes encoding NAD + -dependent malate dehydrogenase, proline-rich protein, secretory peroxidase, lipid transfer protein, fructose biphosphate aldolase (Fbap), raffinose synthase, chloroplast ATPase, 4-coumarate-coenzyme A ligase, and NADP + -dependent ferredoxin reductase under salt stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Abscisic acid-, stress-, and ripening-induced (ASR) proteins are small and heat-stable proteins that have a high hydrophilicity and act as downstream components of a common transduction pathway for sugar (Yang et al, 2005). Among ASR proteins, ASR1 is a plant-specific, highly charged low molecular weight and heat-stable protein whose expression in plants is induced by high salinity, dehydration, and treatment with the plant hormone ABA (Goldgur et al, 2007).…”
Section: Introductionmentioning
confidence: 99%